The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.jvs.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

A contemporary meta-analysis of Dacron versus polytetrafluoroethylene grafts for femoropopliteal bypass grafting

Abstract: Either Dacron or PTFE grafts can be used in femoropopliteal bypass grafting with no significant differences in midterm graft patency at 5 years (49.2% vs 38.4%) when the autologous saphenous vein is unavailable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 22 publications
(25 reference statements)
4
47
0
2
Order By: Relevance
“…A contemporary meta-analysis of femoropopliteal bypass grafts found patency to be 60.2% at 3 years and 49.2% at 5 years. [7] Furthermore, aortofemoral bypass grafts have shown to have 9.4% yearly thrombosis rate and a 5 year patency of 59%. [8] Some of the various techniques for endograft recanalization are included as CDT, Fogarty thrombectomy, and laser recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…A contemporary meta-analysis of femoropopliteal bypass grafts found patency to be 60.2% at 3 years and 49.2% at 5 years. [7] Furthermore, aortofemoral bypass grafts have shown to have 9.4% yearly thrombosis rate and a 5 year patency of 59%. [8] Some of the various techniques for endograft recanalization are included as CDT, Fogarty thrombectomy, and laser recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…All grafts, especially small-caliber synthetic bypass below 6 mm, face the problems of thrombosis, immune rejection, and biodegradation [43]. Although there is no relevant difference according to patency rates between the materials used at present in cardiovascular patients, it has been shown in several in vivo trials that synthetic grafts are inferior to autologous substitutes [44]. Especially for long term applications the patency rates are much lower with nearly 70% (71% of PET and 74% of ePTFE) after one year and 58% (59% of PET and 56% of ePTFE) after three years compared to 90% and 81% for autologous prostheses, respectively [43,[45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported patency rates for above-knee grafts as low as 62% at 3 years and 46% at 5 years [1][2][3] . Abnormal junction haemodynamics, wall shear stress (WSS), suture line injury and material mismatch are the most frequently mentioned factors responsible for graft failure.…”
Section: Introductionmentioning
confidence: 92%